Waiting in Ventimiglia: The French-Italian border between militarization, crisis of hospitality, pandemic management and solidarity - Daminelli, Luca (2022)
This ethnography was conducted on the French-Italian border in Ventimiglia from 2019 until autumn 2021. The previous knowledge of the area allowed to understand how the management by the States of the Covid-19 pandemic has redefined the border device. The article starts with a description of how the border controls operate and continuously change to limit the possibility of border crossing by illegalized migrants. The second part analyses the situation generated in Ventimiglia by the closure of the border as a crisis of hospitality (Lendaro, Rodier, Vertongen 2019), due to the inaction of local institutions (Davies, Isakjee, Dhesi 2017). In the conclusions, the article analyses which are the consequences on migrant subjectivities of the entanglement between the militarization of the border and the denial of reception, that forces to live the experience of waiting in precarious and marginal conditions, opposed by the activities of the solidarity groups in the area.